Analisis Timbulan Sampah Domestik Di Kota Bangkinang - Riki Ablan Yusandre; Jecky Asmura; Aryo Sasmita (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Bangkinang city is the capital of Kampar Regency which consists of urban areas, Bangkinang city and Bangkinang Districts. It has an area of 224.65 Km2 and the population of the two districts is 77,339 inhabitants. The population continues to grow, but waste management facilities such as Temporary Shelter (TPS) provided by the government are not evenly distributed and have not fully served the community in the city of Bangkinang. The population growth of Bangkinang city reaches 2.43% annually. With a population of 77,339 people, the city of Bangkinang has the potential to produce large amounts of waste, which if not managed properly can cause a decrease in the quality and aesthetics of the environment. Therefore it is necessary to calculate the generation of waste as a basis for waste management in the city of Bangkinang. The calculation of waste generation that is carried out refers to SNI 19-3964-1995, the unit of large city waste generation = 2 - 2.5 L / person / day, or = 0.4 - 0.5 kg / person / day, the unit of waste generation medium / small city = 1.5 - 2 L / person / day, or = 0.3 - 0.4 kg / person / day. Based on the results of the calculation of waste generation, Bangkinang city is included in the category of small cities, it is found that the waste generation is 154,7 m3 / day. Key words: Bangkinang City, Waste Generation, Domestic Waste.